Pengaruh Model Problem Based Le Pengaruh Model Problem Based Learning Terhadap Kemampuan Penalaran Matematis Mahasiswa Universitas HKBP Nommensen Pematangsiantar: Pengaruh Model Problem Based Learning Terhadap Kemampuan Penalaran Matematis Mahasiswa Universitas HKBP Nommensen Pematangsiantar - Theresia Monika Siahaan; Rianita Simamora (PendIPA Journal of Science Education, 2024)
This research was a quasi-experimental research with a one shot case study research design with the sample in this research being students of the Mathematics Education Study Program at HKBP Nommensen Pematangsiantar University, totaling 30 people obtained using the Simple Random Sampling technique, namely the PM A1 group. The purpose of this research is to find out how the Problem Based Learning model influences mathematical reasoning abilities. The research results showed that the average post-test result of students' mathematical reasoning ability = 64.77, meaning that mathematical reasoning ability is classified as good and the average result of observation of the Problem Based Learning model = 71.1, meaning that learning is implemented using Problem Based Learning using the Problem Based Learning model has been done well. Based on the value of students' mathematical reasoning abilities, the regression equation Y ̂ = 26.38 + 0.54X, b = 0.54, means that if the Problem Based Learning model increases by 1 unit, it will increase students' mathematical reasoning abilities by 0.54 units. To test the linearity of the regression, it was obtained that Fcount < Ftable or 0.009 < 3.65, meaning that there is a linear and meaningful relationship between the Problem Based Learning model and mathematical reasoning abilities. The results of the regression significance test obtained by the sample using the F test obtained Fcount > Ftable or 28 > 4.20 3.65, meaning that there is an influence between the Problem Based Learning model and mathematical reasoning abilities. From the results of Product Moment correlation calculations, rcount = 0.916, meaning that there is a very strong or very high relationship between the learning model and mathematical reasoning abilities. To test the significance of the correlation coefficient, tcount > ttable or 12.085 > 2.048, meaning there is a very strong and meaningful relationship between the Problem Based Learning model and mathematical reasoning abilities. And the results of calculating the coefficient of determination obtained r2 = 97.65%, meaning that mathematical reasoning ability is influenced by the Problem Based Learning model by 83.91% while the remaining 16.09% is influenced by other factors. From the results of the research above, it can be concluded that there is an influence of the Problem Based Learning model on reasoning abilities. So it is hoped that the Problem Based Learning model can be used as an alternative learning to improve mathematical reasoning abilities.